Development of Teaching Material on Non-Central Collisions Based on Problem Based Learning Model Assisted by PhET Simulations - Shelly Salista Rahmayanti; Budi Astuti; Putut Marwoto (Universitas Negeri Padang, 2026)
Physics learning on non-central collisions is often challenging because students must understand abstract concepts and dynamic interactions, while existing instructional Material generally provide limited opportunities for conceptual exploration and problem-solving. To address this issue, this study developed instructional Material based on the Problem-Based Learning model supported by PhET simulations. This study aims to identify the characteristics, level of suitability, and student responses to the developed instructional Material. This study employs a Research and Development (R&D) method using the 4D model, which includes the Define, Design, Develop, and Disseminate stages. The research instruments included expert validation sheet, readability test sheets, and student response questionnaire. The results showed that the developed instructional Material integrated the PBL framework with PhET simulations, enabling students to solve contextual problems, explore concepts, and build understanding independently. The feasibility test yielded a score of 91.25%, categorized as “highly feasible” based on content, presentation, language, typography, and visual design. The readability feasibility test obtained 91.79%, categorized as “highly feasible,” while student readability reached 98%, categorized as “easy to understand.” Student feedback on the use of these instructional Material reached 89.5%, categorized as “very good.” Based on these results, the developed instructional Material have strong potential as an effective learning resource for teaching non-central collisions in physics.